The Effect of Quality of Work Life, Sanctions, Compensation Satisfaction and Supervision on Employee Work Discipline at the Ministry of Agrarian Affairs and Medan City Spatial Planning / National Land Agency - Ritonga, Ilham Mubaraq; Suyar, Annisha Suvero; Anggreini, Monica (CV. Utility Project Solution, 2023)
This study aims to investigate the influence of Quality of Work Life, Sanctions, Compensation Satisfaction, and Supervision on Employee Work Discipline at the Ministry of Agrarian Affairs and Spatial Planning Agency of Medan City/National Land Agency. This study was conducted to understand how these factors are interconnected and have the potential to influence employee work discipline in that environment. This research methodology uses a quantitative approach with a survey as the data collection tool. A sample was drawn from employees in the agency, and the data was analyzed using appropriate statistical techniques, including regression analysis. The results of this study show that Quality of Work Life (QWL) contributes positively to Employee Work Discipline, suggesting that a good work environment can improve work discipline. In addition, Compensation Satisfaction also has a significant positive impact on work discipline, indicating that employees who are satisfied with their compensation are more likely to be disciplined in carrying out their duties. Sanctions and Supervision also play an important role in influencing work discipline, where effective supervision and consistent application of sanctions can improve work discipline. This research has practical implications for management at the Ministry of Agrarian Affairs and Medan City Spatial Planning Agency/National Land Agency, who can use these findings to improve work discipline.